IDENTIFIKASI RISIKO BERKURANGNYA JAMINAN KEHALALAN PRODUK MINUMAN SALAK DI INDUSTRI KECIL MENENGAH (IKM) SALAKMAS - Adhitama, Lukman; Kurniawan, Akbar; Aulia, Arina Rijki; Elkhanna, Farah Asifi (PPPM POLTESA, 2023)
The growth of innovations in the culinary industry also requires business owner to pay attention to the quality assurance of the products they produce. One of the things that needs to be considered as part of product quality assurance is the halal status of the product itself. The importance of the halal aspect of products requires Salakmas Small and Medium Industries (IKM) to pay attention to the snake fruit drinks they produce so that they are safe from the risk of reducing product halal guarantees. Through this research, the results were obtained that in terms of the raw materials in the recipe and the production process of snake fruit drinks, it can be categorized as halal raw materials. However, through analysis carried out using the Failure Mode and Effect Analysis method, the results were obtained that the industrial management managed by IKM Salakmas has 7 risks that have the potential to disrupt the halal guarantee of the products it produces. From these seven risks, 1 risk was obtained which has the greatest influence on the halalness of the product, so it needs to be paid attention to by IKM Salakmas, where the industry manager must always carry out quality management on the salak raw materials that he uses as raw material for the snake fruit drinks he produces.